Peran Kepemimpinan dalam Meningkatkan Kinerja Anggota PMR di Lingkungan Sekolah - Fitri Ana Daulay; Fizri Aspika Putri Pane; Mutiara Indah Kharisma; Usiono Usiono (Lembaga Pengembangan Kinerja Dosen, 2025)
The optimal performance of PMR members is very dependent on the quality of leadership in the organization. Effective leadership can increase members' motivation, discipline and skills in carrying out tasks and achieving organizational goals. The aim of this research is to identify and analyze the role of leadership in improving the performance of Youth Red Cross (PMR) members in the school environment. The research method uses a qualitative approach and involves literature study, data collection techniques use literature research which involves explanations of books and articles that are relevant to the object of study which includes the role of leadership in improving the performance of Youth Red Cross (PMR) members in the school environment. From this research, the author found three results: first, the role of leadership in PMR, second, ways to improve the performance of PMR members in schools, and third, challenges in PMR leadership in schools.